Retrospective study on prevalence of anaemia among pregnant women at booking in a health care centre in Yadwad, Dharwad, Karnataka, India - BU, Prathvim Raj; Mangasuli, Vijayalaxmi (International Journal Of Community Medicine And Public Health, 2016)
Background: Anaemia in pregnancy is one of the major risk among them. This is associated with abortions, premature births, postpartum haemorrhage and low birth weight. Thus anaemia is considered as one of the most frequent complications of pregnancy and there is need of early detection. Methods: Retrospective record based study conducted at Rural Health Training Centre, Yadwad, Dharwad for a period of one month from October to November. Data regarding pregnancy are collected from September 2014 to October 2015 by referring the records maintained at RHTC. Data was analysed using SPSS. Results: A total of 142 pregnant women were registered for ANC care during this one year period. Majority (76.1%) belonged to the age group of 20-25 years and 92.1 were Hindu by religion. 54.9% of pregnant women were registered during first trimester followed by 23.2% who had registered during second trimester and rest at third trimester. Prevalence of anaemia in the present study was found to be 75.2% with 121 cases among which 101 cases were mild form, 19 cases were moderate form and only 1 case was of severe form with Haemoglobin level below 7g/dl. The study didn’t show any significant association between anaemia and age of present pregnancy, trimester of booking/registration, birth interval from last pregnancy and parity when analysed using chi square test with yates correction at significance at p<0.05. Conclusions: There is high prevalence (85.2%) of anemia among pregnant women. It was also noted that 45.1% of the pregnant women registered after first trimester of pregnancy. Hence leading to late acceptance of antenatal care and iron and folic acid supplementation which is given to reduce the cases of anemia in pregnancy.